Α-Synuclein deficiency promotes neuroinflammation by increasing Th1 cell-mediated immune responses. Issue 1 (December 2016) - Ettle, Benjamin; Kuhbandner, Kristina; Jörg, Stefanie; Hoffmann, Alana; Winkler, Jürgen; Linker, Ralf
Abstract Background Increased α-synuclein immunoreactivity has been associated with inflammatory activity in multiple sclerosis (MS) lesions, but the function of α-synuclein in neuroinflammation remains unknown. The aim of this study was to examine the role of α-synuclein in immunological processes in murine experimental autoimmune encephalomyelitis (EAE) as a model of MS. Findings We studied EAE in wildtype (aSyn+/+ ) and α-synuclein knockout (aSyn−/− ) mice on a C57BL/6N background. In the spleen and spinal cord of aSyn+/+ mice, we observed a gradual reduction of α-synuclein expression during EAE, starting already in the pre-symptomatic disease phase. Compared to aSyn+/+ mice, aSyn−/− mice showed an earlier onset of symptoms but no differences in symptom severity at the peak of disease. Earlier symptom onset was accompanied by increased spinal cord infiltration of CD4+ T cells, predominantly of interferon-γ-producing T helper 1 (Th1) cells, and reduced infiltration of regulatory T cells, whereas antigen-presenting cells were unaltered. Pre-symptomatically, aSyn−/− mice exhibited hyperproliferative CD4+ splenocytes consistent with increased splenic interleukin-2 mRNA expression, resulting in increased numbers of Th1 cells in the spleen at the onset of symptoms. Conclusions Our findings indicate a functional role of α-synuclein in early EAE by increasing Th1 cell-mediated immune response.